EFEKTIFITAS SOSIALISASI MAL OLEH KONSELOR ASI SEBAGAI SALAH SATU UPAYA PENCEGAHAN UNMEET NEED KB - luluk rosida (Midwifery Journal: Jurnal Kebidanan UM. Mataram, 2019)
Abstract Lactation amenorrhea method (LAM) is an alternative that can be used by women who experienced the unmet need for family planning to breastfeed cause delays recovery of fertility after childbirth and can be used as a natural contraceptive methods. The purpose of this study was to determine the effectiveness of the socialization of LAM by a breastfeeding counselor to efforts to reduce unmeet need in Yogyakarta. This quasi study uses the design of Non-Equivalent Control Group, which compares the return of menstruation to postpartum mothers with exclusive breastfeeding given LAM socialization by ASI counselors with postpartum mothers who were not given LAM socialization by ASI counselors. Women who are exclusively breastfeeding will in principle get longer menstrual initiation than those who do not exclusively breastfeed their babies. The sample in this study were mothers who had just given birth at the Community Health Center hospitalized in Yogyakarta. Bivariate analysis using the whtney man test. The results showed that there were differences in the return of menstruation in postpartum mothers who were given LAM  socialization by ASI counselors with postpartum mothers who were not given LAM socialization.